Textualización, mistificación y el poder de la estructura - Crapanzano, Vincent (Revista de Antropología Social, 2008)
In this paper I argue that many of the contributions to the Writing Culture movement and many of its critiques were caught in a “textual illusion.” By “textual illusion,” I mean the so framing a text that it overrides conceptually its contexts of production and its aftermath and becomes an independent artifact, which in the extreme -as in Geertz’s notion of culture as an ensemble of texts- becomes the model for what it depicts. So framed, the text permits a series of -critical- self-reflective maneuvers, including seemingly transgressive ones, that, as illuminating as they may be, inevitably mask some of the presuppositions that constitute the text’s textuality and the range of responses to it. Among these masked presuppositions are attitudes toward language and language usage; in case in point, the emphasis on the semantico-referential function and the consequent privileging of mimetic representation at the expense of other linguistic functions, including the pragmatic, the poetic, and the phatic. Coupled with a culture/historical-specific tendency to de-historicize the text, mimetic representation becomes the paramount textual focus and, in consequence, culture, modeled on text, is articulated in timeless, representational fashion. I argue that the emphasis on texts, which characterized the Writing Culture movement, limited consideration of both the circumstances of textual production and the ways in which the texts themselves constitute their own readings and interpretations. In short, I suggest that ethnography and the social sciences in general should focus critical attention on the particular reading/interpretive practices they cultivate and privilege.
Keywords: Textual illusion; Writing Culture movement; Representation; Pragmatics; Textual production; Models of culture